2017
DOI: 10.1186/s12969-017-0213-x
|View full text |Cite|
|
Sign up to set email alerts
|

A national cohort study on pediatric Behçet’s disease: cross-sectional data from an Italian registry

Abstract: BackgroundBehçet’s disease is a rare multi-systemic inflammatory disease with unknown etiology which involves principally oral and genital mucosa, skin and eyes. Average age at onset of the disease is about 25-30 years, but it may be diagnosed before the age of 16. It is not very rare in Italy, even though there are limited data concerning epidemiology. Aim of this study is to describe the baseline data of an Italian cohort of patients with as having BD or probable BD.MethodsWe described the baseline data of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
86
2
9

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(103 citation statements)
references
References 23 publications
(29 reference statements)
6
86
2
9
Order By: Relevance
“…Other BD classification criteria have been developed for more robust diagnoses. The ICBD have been validated in JBD patients with sensitivities that range from 70 to 80%, but specificity data are absent [22, 23]. The PEDBD criteria were developed for children, and they have a sensitivity of 73.5% and a specificity of 97.7% [4, 21].…”
Section: Discussionmentioning
confidence: 99%
“…Other BD classification criteria have been developed for more robust diagnoses. The ICBD have been validated in JBD patients with sensitivities that range from 70 to 80%, but specificity data are absent [22, 23]. The PEDBD criteria were developed for children, and they have a sensitivity of 73.5% and a specificity of 97.7% [4, 21].…”
Section: Discussionmentioning
confidence: 99%
“…This is a rare, sporadic, multi-systemic disease with undetermined cause. The main clinical features are constitutional symptoms and recurrent fever, oral aphthous, genital ulcers, with gastrointestinal, musculoskeletal, neurological, and vascular involvement [54].…”
Section: Behcet's Diseasementioning
confidence: 99%
“…Following publication of the original article [ 1 ], the authors reported that the names of two institutional authors – EUROFEVER and the Paediatric Rheumatology International Trials Organisation (PRINTO) – had been unintentionally omitted in the final online version of the manuscript. The corrected author list is shown in this Correction.…”
Section: Correctionmentioning
confidence: 99%